A qualitative study of Telehealth patient information leaflets (TILs): are we giving patients enough information? - Reem Kayyali; Iman Hesso; Evelyn Ejiko; Shereen Nabhani Gebara (BMC, 2017)
Abstract Background The provision of patient information leaflets regarding telehealth has been perceived by potential consumers as a strategy to promote awareness and adoption of telehealth services. However, such leaflets need to be designed carefully if adoption and awareness among potential users is to be promoted. Therefore, the aims of this study were: first, to see how telehealth was portrayed in some of the existing telehealth leaflets (THLs). Second, to explore patients' perceptions of the existing THLs and their engagement with the concept and how THLs can be optimised. Methods A two-step approach was employed to address the aims of this study. The first phase involved the use of discourse analysis to compare 12 electronically and publically available THLs, with the existing THL guidance "Involve Yorkshire and Humber". The second phase involved conducting 14 semi-structured interviews with potential telehealth users/patients to gauge their perception and engagement with the concept, using the two leaflets that were mostly matching with the guidance used. Six interviews were audio-recorded and eight had detailed jotted notes. The interviews were transcribed and thematically analysed to identify key themes. Results The discourse analysis showed certain gaps and variations within the screened leaflets when addressing the following aspects: cost of the telehealth service, confidentiality, patients' choices in addition to equipment use and technical support. Analysis of the interviews revealed patients' need for having clear and sufficient information about the telehealth service within the THLs; in addition to, patients' preference for the use of simpler terminologies for telehealth description and the provision of clear simple texts with pictorial presentations. The interviews also revealed certain limitations against adoption of telehealth by the participants, such as: lack of privacy and confidentiality of information, fear of technology breakdown and equipment failure, loss of face-to-face contact with healthcare professionals and being too dependent on the telehealth service. Conclusion The current study showed a great variation among the screened THLs and highlighted certain gaps within the content and presentation of these leaflets. However, the study also highlighted certain key issues to be considered when designing THLs in the future to enhance telehealth uptake and use by patients.